2020
DOI: 10.18666/jorel-2020-v12-i4-10271
|View full text |Cite
|
Sign up to set email alerts
|

Wilderness-Based Professional Development for Educators: Exploring Outcomes and Influential Programmatic Elements

Abstract: The personal and professional outcomes of experiential wilderness-based professional development programs for K-12 educators have not been adequately evaluated. This study used openended survey questions to identify a range of personal (i.e., self-awareness, new perspectives, self-confidence) and professional (i.e., changes in classroom practices, appreciation for educational practices, improved classroom culture) outcomes. Educators also identified the programmatic elements that were most influential to both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The NCOBEI program utilizes the wilderness setting as the primary programming element to facilitate educators’ initial learning experience. Just as wilderness settings in non-PD programs have been associated with a range of participant outcomes (Holland et al, 2018; Thomsen et al, 2018), a recent study (Holland et al, 2020) found the wilderness setting to exert the greatest influence on both personal and professional development outcomes in EWBPD programs for educators.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The NCOBEI program utilizes the wilderness setting as the primary programming element to facilitate educators’ initial learning experience. Just as wilderness settings in non-PD programs have been associated with a range of participant outcomes (Holland et al, 2018; Thomsen et al, 2018), a recent study (Holland et al, 2020) found the wilderness setting to exert the greatest influence on both personal and professional development outcomes in EWBPD programs for educators.…”
Section: Discussionmentioning
confidence: 99%
“…Minor programmatic changes may have been implemented each year of the training exposing educators to different training elements. However, based on previous research investigating specific influential elements of EWBPD programs that educators associate with outcomes received (Holland et al, 2020), all educators in our sample were exposed to the most frequently indicated influential programming elements (an immersive wilderness experience, participating with colleagues, continued forms of follow-up).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations